HUBUNGAN ANTARA SELF-ESTEEM DAN PERILAKU ACADEMIC DISHONESTY MAHASISWA FIP UNNES DENGAN MEDIATOR PEER PRESSURE - Febriyanti, Rosalina (Intuisi : Jurnal Psikologi Ilmiah, 2009)
The research is aimed at examining the correlation between self-esteem and academic dishonesty behavior mediated by peer pressure, as proposed hipothesis. The subject of this research were 212 students of FIP UNNES graduation of Â 2006 to 2008. Sampling technique which is used is stratified proportional random sampling. The data collection was done using academic dishonesty behavior questionnaire, self-esteem scale, and peer pressure scale. Hypothesis is tested by mediator analysis. The result indicate that there was significant correlation between self-esteem dan academic dishonesty behavior mediated by peer pressure (b= -0,1173, p<0,05) at FIP UNNES students. Low peer pressure will lower academic dishonesty behavior and the opposite.